Dinamika Fiskal Daerah: Dampak Gross Regional Domestic Product, Local Revenue dan Dana Alokasi Umum terhadap Belanja Modal di Provinsi Sumatera Utara - Bima Hardi; Della Amalia Vada (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
The purpose of this study is to uncover empirical evidence of the influence of regional income, namely gross regional domestic product (GRDP), regional original income (PAD), and General Allocation Fund (DAU) on capital expenditure in North Sumatra Province. The population of this study consists of 33 regencies/cities in North Sumatra with data from the 2019-2023 period. Using a panel data regression method with a fixed-effects model (FEM) via the Eviews-13 application, the results indicate that RDRP, PAD, and DAU simultaneously influence capital expenditure, as evidenced by the calculated F-value (10.40710) exceeding the critical F-value (2.93). Partially, the GRDP variable has a positive and significant effect on capital expenditure with a t-value (2.9113257) > t-table (2.04227). sPartially, the DAU variable has no significant effect on capital expenditure, with a t-value of (0.326144) < t-table (2.04227). PAD contributes the most to capital expenditure. This finding indicates that regional fiscal autonomy through increased PAD and local economic productivity plays an important role in driving capital expenditure capacity.